PRIMO Monte Carlo Simulation and One-dimensional Gamma Index Analysis as a Tool to Validate Experimentally Measured Beam Data and Treatment Planning System Calculated Dose Distribution - Ngangom Robert; Ranjit Singh; Arun S Oinam; Budhi Singh; Gaurav Trivedi (Journal of Medical Physics)
Purpose: The purpose of this study was to validate experimentally measured beam data, and treatment planning system (TPS) calculated volumetric modulated arc therapy (VMAT) three-dimensional (3D) dose distribution using PRIMO Monte Carlo (MC) simulation and one-dimensional (1D) gamma index analysis. Materials and Methods: The PRIMO code simulates the percentage depth dose (PDD) and beam profiles across varying field sizes in water phantoms, which were then compared with the ion chamber-measured beam characteristics using 1D gamma analysis. For the VMAT 3D dose distribution, the computed tomography scan of the anthropomorphic pelvis phantom was used for dose calculation and simulation in Eclipse TPS and PRIMO, respectively. Then, the doses of the target and organ at risk were compared with 1D gamma index analysis. Results: The results show that the PDD passed the 1D gamma index above 95% of all evaluated points at 2%/2 mm criteria. There was no significant difference between the mean values of measured and MC-simulated PDD at all field sizes. The results were statistically significant as P < 0.05. For beam profile at a 10 cm depth along in-line (in-plane) and cross-line (cross-plane) directions, above 95% of all the evaluated points passed the 1D gamma index at 3%/3 mm. The matching of dose volume histogram (DVH) of TPS calculated and PRIMO simulated DVH passed 2%/2 mm and 3%/3 mm gamma index passing criteria. Conclusions: Based on this study’s findings, PRIMO MC simulation can validate experimentally measured medical linear accelerator beam data and TPS 3D dose distribution with acceptable agreement using 1D gamma analysis.